Pipestone : my life in an Indian boarding school - Fortunate Eagle, Adam, 1929- (University of Oklahoma Press, 2010)
Best known as a leader of the Indian takeover of Alcatraz Island in 1969, Adam Fortunate Eagle now offers a memoir of his years as a young student at Pipestone Indian Boarding School in Minnesota. He lives up to his reputation as a "contrary warrior" by disproving the popular view of Indian boarding schools as bleak and prisonlike. Fortunate Eagle attended Pipestone between 1935 and 1945, just as Commissioner of Indian Affairs John Collier's pluralist vision was reshaping the federal boarding school system to promote greater respect for Native cultures and traditions.